The development of methods for the determination of residues of the insecticide pymetrozine in water, soil, cucumber and rape - Zayats, Mikhail F.; Leschev, Sergey M. (Journal of the Belarusian State University. Chemistry, 2019)
Based on the literature data on the solubility of pymetrozine in water and organic solvents, as well as experimental data on the extraction of pymetrozine from water, soil and plant matrices, the optimal conditions for the extraction of pymetrozine from water; soil; cucumber; rape seeds, oil and green pods were selected. The conditions for cleaning extracts were selected as well. At the first stage, acetonitrile, a mixture of dichloromethane – isopropanol, or a mixture of dichloromethane – methanol in the presence or absence of inorganic salts were used for extraction of the pesticide. Pymetrozine was found to be a highly hydrophilic substance. For the purification of extracts of pymetrozine from plant matrices the extraction systems hexane – 0.02 mol/L aqueous solution of orthophosphoric acid, hexane or chloroform – aqueous solutions of ammonium sulfate were successfully used. The samples, obtained after this treatment, were pure enough to determine the residual amounts of pymetrozine in them at the maximum residue level (MRL), determined in Russia and the countries of the European Union, or lower using widespread liquid chromatography with diode-array (ultraviolet) detection.
Keywords: solvent extraction; pymetrozine; sample preparation method; liquid chromatography; water; soil; cucumber; rape